Solar Preheating in Power Plants: An Overview Of The Current State Of The Technology - Ziyu Chen; Dengyu Ba; Kehui zhuang (International Journal of Advanced Science and Computer Applications, 2022)
Utilizing preheating units is one of the most critical ways to improve the performance of thermal power plants. Increasing the overall efficiency of Brayton or Rankine cycles by preheating the air or stream may result in considerable increases in output power and efficiency. When it comes to renewable energy, solar energy is an appealing alternative for use as a source of preheating since it is readily accessible. The current article discusses the use of solar energy for preheating air and steam in thermal power plants, as well as other uses. The performance of the systems is being improved, according to evaluations, as a result of a variety of elements, including the configuration of the reference system, the operating environment, the applied technology, and so on. Aside from improving the overall efficiency of the power plant, the incorporation of a solar preheating system may significantly decrease fuel usage and, as a result, carbon dioxide emissions. Furthermore, owing to the unavailability of solar energy during the night and overcast hours, thermal storage units may improve the system's dependability while also increasing the contribution of solar energy to the system's output.